Thermodynamics, economy and environment analyses and optimization of series, parallel, dual-loop Kalina cycles for double-source heat recovery in cement industry. - Yali Wang; Yongjun Xu; Yongliang Qiu; Shengwang Ning (PLoS ONE)
This research aims to investigate the heat recovery of both suspension preheater flue gas and clinker cooler hot air in cement industry. Three thermodynamic cycles including series Kalina Cycle (S-KC)、parallel Kalina Cycle (P-KC) and dual-loop Kalina Cycle (DL-KC) are introduced for converting dual-source heat resources into power to enhance the system efficiency for cement production process. Firstly, the multi-layer comprehensive evaluation models are established for the three thermodynamic cycles. Then, the parametric studies are implemented to estimate the influences of six key parameters on the system's thermodynamic-economic-environmental performances. Meanwhile, optimization investigations consisting of thermodynamic optimal design (TOD), thermodynamic and economic optimal design (TEOD), and thermodynamic, economic and environmental optimal design (TEEOD) are considered, and the performances of systems and components are compared under three optimal design scenarios. The results prove that, for S-KC, P-KC and DL-KC, the higher net power output (Wnet) can be gained with decreasing condenser outlet temperature and regenerator temperature difference, and increasing evaporator temperature difference and superheat degree, the lower electricity production cost (EPC) can be acquired with decreasing condenser outlet temperature, evaporator temperature difference and regenerator temperature difference, while the less environment impact load (EIL) can be attained with decreasing condenser outlet temperature, regenerator temperature difference and basic ammonia concentration, and increasing superheat degree. In addition, under TOD, TEOD and TEEOD scenarios, DL-KC is the best selection from the thermodynamic, economic and environmental perspectives, with the corresponding Wnet of 7166 kW, 6904 kW and 6838 kW, the EPC of 0.00476 $/kWh, 0.00369 $/kWh and 0.00362$/kWh, the EIL of 0.0597 mPEChina,90/kWh, 0.0599 mPEChina,90/kW and 0.0593 mPEChina,90/kW. It also identifies that the evaporator unit is the key component contributing to exergy destruction and investment cost for three systems, while the pump has the maximum influence on environmental performance.